Intertextual translatability using the example of the German translation of the Ukrainian novel "Twelve Rings" by Yuri Andrukhovych - Höfinghoff-Vornberg, Marina (Traduttologia e Traduzioni, vol. III: Interdisciplinarietà della traduzione, 2021)
This chapter deals with questions of intertextuality and in this context with the problem of the translatability of an intertext. The analysis is carried out using the example of the German translation of the Ukrainian novel Twelve Rings by Yuri Andrukhovich. In the analytical part of the article some intertexts will be identified and explained. It will be analyzed whether these intertexts were recognized in the German translation and how successfully they were communicated to the German readership. A limited number of references from the fields of poetry, advertising and pop culture, which are used as intertextual models in the novel, will be dealt with. The examples are decoded and described to clarify how a communication process between the author and the recipient takes place.